The urban carbon unlocking effect of digital infrastructure construction: A spatial difference-in-difference analysis from “Broadband China” pilot policy - Liang Guo; Lijing Chen; Zhen Yang (PLoS ONE, 2025)
As the foundation and cornerstone of the digital economy, digital infrastructure construction is an indispensable engine for realizing China’s energy-saving and emission-reduction, innovation-driven and low-carbon transformation and development. Investigating the carbon unlocking effect of digital infrastructure construction might hasten the achievement of the dual-carbon goal and the “win-win” scenario of environmental protection and economic growth. However, there is still a gap between whether and how digital infrastructure construction can break the carbon lock-in (CLI). Based on the panel data of 266 prefecture-level cities from 2006 to 2019, this paper takes “Broadband China” policy (BCP) as a quasi-natural experiment, constructs a spatial difference-in-difference (SDID) model to explore its impact on CLI, and further analyzes its transmission mechanism, spatial spillover effect and heterogeneity. The results show that: (1) BCP can break the carbon lock-in in the pilot cities and remains valid after a series of robustness tests. (2) There is a lag in the carbon unlocking effect of BCP, and the effect is gradually significant after 3 years of policy implementation. (3) BCP has a spatial spillover impact on CLI, and it significantly contributes to both nearby and local cities. (4) By encouraging green technical advancement and upgrading industrial structure, BCP breaks the CLI. (5) There is regional heterogeneity and urban characteristic heterogeneity in the carbon unlocking effect of BCP. On this basis, we propose a series of policy recommendations to hasten the implementation of low-carbon transformation and sustainable urban development.